Effects of atorvastatin and artichoke leaf tincture on oxidative stress in hypercholesterolemic rats - Crevar-Sakač, Milkica; Vujić, Zorica; Kotur-Stevuljević, Jelena; Ivanišević, Jasmina; Jelić-Ivanović, Zorana; Milenković, Marina; Markelić, Milica; Vujčić, Zoran (Vojnosanitetski pregled, 2017)
Backgroung/Aim. Since combining conventional drugs with herbal medicinal products is in current research focus and possible of great interest as therapy improvement way, the aim of this study was to determine the effects of well-established antiatherosclerotic drug atorvastatin (CAS number 134523-00-5) and commercially available artichoke leaf tincture (ALTINC), used as combined therapy, as well as to compare effects of these two treatments separately. Methods. Experimental animals were divided into five groups: the group I (the control group of rats fed with standard diet during 11 weeks), and the remaining 4 groups of rats (II, III, IV and V) fed with standard diet during the first week and then with hypercholesterolemic diet during the next 10 weeks. The group II of rats were left without treatment, while in the groups III, IV and V were rats treated per os with atorvastatin (1.15 mg/kg body wright − b.w.), ALTINC (0.1 mL/kg b.w.) and their combination in same doses, respectively, for the last six weeks. Results. The cholesterol rich diet led to pronounced hyperlipidemia which could not be overcame with the therapy. However, the therapy showed positive effects on abdominal aorta wall thickness and parameters of oxidative stress (malondialdehyde − MDA, proxidative-antioxidative balance − PAB) and antioxidative protection (reduced glutathione − GSH, paraoxanase 1 − PON1, superoxide dismutase − SODA SH groups), especially ALTINC was successful in oxidative status improvement. Conclusion. Separate treatments comparison showed that artichoke leaf tincture is very potent antioxidant with beneficial effects in early stages of atherosclerosis. Since atorvastatin and constituents of ALTINC probably have different mechanisms of action, simultaneous use of both therapies could be beneficial but should be further investigated since our results showed that ALTINC is less effective when used in combination with atorvastatin.
Keywords: oxidative stress; cynara scolimus; atorvastatin calcium; atherosclerosis; rats; treatment outcome